Sea‐water circulation on an oolite‐dominated carbonate system in an epeiric sea (Middle Jurassic, Switzerland). Issue 1 (23rd January 2013) - Wetzel, Andreas; Weissert, Helmut; Schaub, Monika; Voegelin, Andrea R.; Föllmi, Karl
Abstract The Middle Jurassic Burgundy carbonate platform occupied a central part of the Central European Epeiric Sea during the Middle Jurassic. The facies architecture of the oolitic calcarenite bodies was affected by tidal currents on the platform and relative sea‐level changes. The δ13C‐values of inorganic carbonates, sampled in biostratigraphic‐defined intervals, do not match very well between closely spaced sections and, hence, are of restricted use for stratigraphic purposes. It appears that the platform interior might have been decoupled from the global carbon pool. Although deposited in a rapidly accumulating setting, the recorded isotope signatures might be affected by some local stratigraphic gaps. Nonetheless, the carbon isotope data imply lateral changes of the platform waters; these appear to be related to the position on the platform and to the sediment dispersal pattern, as evidenced by clay minerals. Adjacent to the eastern margin of the platform, detrital chlorite and illite occur in considerable proportions, both ascribed to a boreal source to the east and the north‐east. In contrast, smectite‐rich mixed‐layer clay mineral content increases significantly towards the platform interior, pointing to a delivery from the north‐west. All these data are suggestive of an overall clockwise current pattern in the Central European Epeiric Sea during the Middle Jurassic.